THE APPLICATION OF THE DISCOVERY LEARNING MODEL IN THE INDEPENDENT CURRICULUM TO STUDENTS' CRITICAL THINKING SKILL - Retno Triwoelandari; Ikhwan Hamdani; Dina Fauziyyah Qoyyimah Ajhari Hakim (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2024)
Abstract This study aims to see the effect of applying discovery learning model in the Merdeka Curriculum on the critical thinking skills of grade 5 students in science subjects. This study uses a quantitative approach in the type of pre-experimental design in the form of a one-group pretest-posttest design. Data was collected using instruments in the form of pretests and posttests. This research was conducted at SD IT Baitussalam grade 5 in Tajurhalang District, Bogor Regency. The data obtained were analysed using paired sample t-test. The results of the study stated that there was an effect of the application of the independent curriculum discovery learning model on the critical reasoning of grade 5 students in science subjects. After the implementation of the independent curriculum, students' critical reasoning skills increased. The implication of this research confirms the importance of discovery learning as an effective learning model in improving students' critical thinking skills.